Pengaruh Perbandingan MAA dan EGDMA terhadap Kapasitas Adsorpsi IIPs-Pb(II) - Ananta Nazira Meliano; Alizar Ulianas (MASALIQ, 2026)
The successful synthesis of Ion Imprinted Polymers (IIPs) is strongly determined by the selection and ratio of the functional monomer and crosslinker because these two components directly affect the resulting adsorption capacity. An inappropriate composition, whether too low or too high, can reduce adsorption performance, because a low amount tends to produce a less stable polymer structure, whereas an excessive amount can increase nonspecific interactions and form an overly dense polymer structure. This study aims to determine the optimum ratio between the functional monomer and crosslinker in the synthesis of IIPs-Pb(II). The synthesis was carried out through the photopolymerization method by varying the amounts of MAA and EGDMA, then evaluating their performance based on the adsorption capacity toward Pb(II) metal ions. The concentration of adsorbed Pb(II) metal ions was analyzed using Atomic Absorption Spectroscopy (AAS). The results showed that the optimum ratio of MAA and EGDMA was 0.01 mol : 0.015 mol, with adsorption capacities of 0.79 mg/g and 0.43 mg/g, respectively. This optimum ratio was subsequently used to produce IIPs-Pb(II) that were effective in adsorbing Pb(II) metal ions. These findings contribute to clarifying the relationship between the composition of the functional monomer and crosslinker and the characteristics of the resulting polymer. Thus, IIPs-Pb(II) have the potential to be applied in the process of selectively detecting and removing Pb(II) metal ions, especially on an industrial scale.